The fantastic in Alvaro Miranda's "La risa del cuervo": an attempt for deconstructing the inclusive/exclusive of the national Colombian narratives - Castillo Balmaceda, Sandra Milena (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article discusses the construction of a fantastic perspective that Álvaro Miranda makes in his first novel La risa del cuervo. I claim that the author’s “bizarre” perspective is responsible for the inclusion of fantastic elements that aim to arouse in the reader an “uncertain” perception of the literary world recreated in the novel. My main hypothesis is that Miranda taps into fantastic elements in order to cope with the pressure put by both the aesthetic field -the inadequacy of magic realism to communicate aesthetically Latino American reality in the seventies- and the social field - the need to deconstruct the inclusive / exclusive narratives that were used to build Colombian nation- and that the author also intends to motivate the readers to assume a liminal view of reality that allows them to question those narratives.
Keywords: Fantastic literatura; deconstruction; liminal perspective; parallel worlds